Pregnancy fitness - Paolo, Julia Di 1973- Reg. PT; Vopni, Kim; Montpetit-Huynh, Samantha 1970- (Human Kinetics, 2019)
"Pregnancy Fitness provides information and techniques to help women build and maintain physical fitness to have a healthy pregnancy. It also provides exercises to enable them to gain the functional fitness skills they will need to be prepared for the everyday physical demands of motherhood. It details information about the physical changes that occur during pregnancy, programs of physical fitness for all stages of pregnancy, physical training to promote a healthy labor and delivery, and tips for new mothers seeking to restore their core muscle function as well as to return to a regular exercise and fitness routine. Exercise programs for all phases include strength and flexibility drills as well as tips for incorporating walking, water fitness, and other activities. Designed for all women, from those who have had little or no experience with physical fitness to those who are seasoned athletes and exercisers, it is a valuable resource for women's health and fitness."--